High-Mobility Group Box-1 Is Associated With Obesity, Inflammation, and Subclinical Cardiovascular Risk Among Young Adults: A Longitudinal Cohort Study. Issue 11 (November 2020) - Chen, Li; Zhu, Haidong; Su, Shaoyong; Harshfield, Gregory; Sullivan, Jennifer; Webb, Clinton; Blumenthal, James A.; Wang, Xiaoling; Huang, Ying; Treiber, Frank A.; Kapuku, Gaston; Li, Wenjun; et al.
Abstract : Objective: We aimed to characterize circulating HMGB1 (high-mobility group box-1) levels, one of the better-characterized damage-associated molecular patterns, with respect to age, sex, and race in the general population, and investigate the longitudinal associations of HMGB1 with inflammatory markers, obesity, and preclinical markers of cardiovascular disease. Approach and Results: The analyses included 489 participants (50% Blacks, aged 24.6±3.3 years at the first visit) with up to 4 follow-up visits (1149 samples) over a maximum of 8.5 years. Systolic blood pressure, diastolic blood pressure, carotid-femoral pulse wave velocity, and carotid intima-media thickness together with plasma HMGB1, hs-CRP (high-sensitivity C-reactive protein), IFN-γ (interferon-γ), IL-6 (interleukin-6), IL-10 (interleukin-10), and TNF-α (tumor necrosis factor-α) were measured at each visit. At baseline, plasma HMGB1 concentrations were higher in Blacks compared with Whites (3.86 versus 3.20 ng/mL, P <0.001), and in females compared with males (3.75 versus 3.30 ng/mL, P =0.005). HMGB1 concentrations increased with age ( P =0.007), and higher levels of obesity measures ( P <0.001). Without adjustment for age, sex, race, and body mass index, HMGB1 concentrations were positively associated with hs-CRP, IL-6, TNF-α, systolic blood pressure, diastolic blood pressure, and carotid-femoral pulse wave velocity ( P <0.05) but not IL-10, IFN-γ or carotid intima-media thickness. After covariate adjustments, the associations of HMGB1 with hs-CRP, and carotid-femoral pulse wave velocity remained statistically significant ( P <0.05). Conclusions: This study demonstrates the age, sex, and race differences in circulating HMGB1. The increasing circulating concentrations of HMGB1 with age suggest a potential role of HMGB1 in the pathogenesis of chronic low-grade inflammation, obesity, and subclinical cardiovascular disease risk. Graphic Abstract: A graphic abstract is available for this article.